Lipase catalysed resolution of the Lotrafiban intermediate 2,3,4,5-tetrahydro-4-methyl-3-oxo-1H-1,4-benzodiazepine-2-acetic acid methyl ester in ionic liquids: comparison to the industrial t-butanol process - Roberts, NJ; Seago, A; Carey, JS; Freer, R; Preston, C; Lye, GJ (ROYAL SOC CHEMISTRY, 2004)
The Candida antarctica lipase B ( Novozyme 435) catalysed resolution of 2,3,4,5-tetrahydro-4-methyl-3-oxo-1H-1,4-benzodiazepine-2-acetic acid methyl ester (SB-235349), a key Lotrafiban intermediate, has been investigated in six ionic liquids including [BMIM][PF6] and [BMIM][N(SO2CF3)(2)]. The initial rate and final yield of the reaction have subsequently been determined in [ BMIM][ PF6] as a function of initial substrate concentration (5-40 g L-1), temperature (25-100 degreesC) and initial water content (3-15% H2O w/w). In each case the results have been compared to those obtained for the optimised industrial process operated in t-butanol (88% v/v). Simply replacing the organic solvent with an ionic liquid under otherwise identical reaction conditions reduced the rate of conversion. However, exploiting the increased solubility of the substrate in ionic liquids and the ability to operate at higher temperatures increased the overall rate of reaction by a factor of four while maintaining the same overall yield of 47%. In each case the ee of the product was 99%. Further experiments demonstrated the ability to re-use the enzyme over 10 reaction cycles and suggested that solute mass transfer in ionic liquids might be an issue for reactions carried out at larger scale. Overall the results suggest that ionic liquids can be very favourable reaction media for industrial bioconversion processes, which also overcome many of the safety and environmental concerns of conventional organic solvents.